ANALYSIS OF AL-LAJNAH AL-DAIMAH LI AL-BUHUS AL-ILMIYAH WA AL-IFTA FATWA RELATED TO THE PHENOMENON OF DOWRY MEMORIZATION OF AL-QUR'AN - IRAWAN, IBNU (Nurani, 2019)
The millennial generation lately, many who give dowry marriage outside the habits of society in general (a set of prayer tools or rings), but dowry in the form of memorization of the al-Qur’an. The opinion that developed at this time was that the dowry was more stable and primary compared to other dowries. There are concerns about the loss of women's rights because the dowry is not material. Then the giving of the dowry for memorizing the al-Qur’an needs to be reviewed with an appropriate legal formulation. Responding to this phenomenon, the Saudi Arabian fatwa institute also issued a fatwa related to the ruling on memorizing the al-Qur'an. This research is a literature review using an empirical juridical approach, while the data collection method was done through documentation and interviews. This study found that the phenomenon of giving the Dowry memorization of the al-Qur’an was a problem that had occurred during the time of the Prophet, but has reappeared lately with opposing motives and backgrounds. Then the purpose of this study is to bring up and clarify the legal status of the phenomenon. The results showed that the law of giving dowry in the form of memorizing the al-Qur'an was not permitted. Keywords: Dowry, Memorization of the Qur'an, Al-Lajnah al-Daimah Li al-Buhus al-IlmiyahWa al-Ifta.